2021
DOI: 10.3390/ijerph18189714
|View full text |Cite
|
Sign up to set email alerts
|

Does Reflection on Everyday Events Enhance Meaning in Life and Well-Being among Emerging Adults? Self-Efficacy as Mediator between Meaning in Life and Well-Being

Abstract: In recent years, the issue of the meaning in life has aroused particularly great interest in researchers considering the question of whether and how, using simple interventions, outside the therapeutic office, the sense of meaning in life and well-being can be strengthened. The aim of this study was to explore whether interventions based on reflection on everyday, stressful situations can contribute to fostering the sense of meaning in life and psychological well-being among emerging adults. Additionally, we a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 62 publications
(64 reference statements)
0
4
0
Order By: Relevance
“…11 Of interest, the ability to find purpose in life and a developed sense of direction requires engagement in self-reflective practices. 11,47 Together, it is conceivable that, instead of preventing the accumulation of pathologic changes (i.e., providing resistance 16 ), self-reflection may contribute to the development of efficient neural systems that allow one to maintain cognition even in the face of accumulating amyloid pathology (i.e., resilience 16 ). Indeed, in our exploratory analyses', associations between self-reflection and global cognition and glucose metabolism remained largely unchanged following inclusion of self-reflection-by-amyloid deposition interactions.…”
Section: Discussionmentioning
confidence: 99%
“…11 Of interest, the ability to find purpose in life and a developed sense of direction requires engagement in self-reflective practices. 11,47 Together, it is conceivable that, instead of preventing the accumulation of pathologic changes (i.e., providing resistance 16 ), self-reflection may contribute to the development of efficient neural systems that allow one to maintain cognition even in the face of accumulating amyloid pathology (i.e., resilience 16 ). Indeed, in our exploratory analyses', associations between self-reflection and global cognition and glucose metabolism remained largely unchanged following inclusion of self-reflection-by-amyloid deposition interactions.…”
Section: Discussionmentioning
confidence: 99%
“…Sharing narratives more broadly has also been studied to examine its numerous benefits on individuals' well-being (Adler et al, 2016), including contributing to both personal and social change (Rutledge, 2016). When examining developing personal narratives as a type of self-reflection practice, including through guided prompts, research has shown that it can support overall well-being, mental health, social connectedness, purpose in life, and self-efficacy (Agnew, 2022;Czyżowska & Gurba, 2021;Frugé & Drutz, n.d., Koshy et al, 2017;Strumm, 2022).…”
Section: Narratives and Storytellingmentioning
confidence: 99%
“…Finally, and with direct relevance to this study, self-reflection has been described as a practice that can enhance a leader's competency (Goleman et al, 2002). Additionally, guided reflective practices have been suggested as a method of developing leadership skills (Roberts, 2008) while they can also be supportive of psychological wellbeing, social connectedness, purpose in life, and self-efficacy (Czyżowska and Gurba, 2021).…”
Section: Leadership and Reflection Practicesmentioning
confidence: 99%